Atypical Endobronchial Carcinoid with Postobstructive Pneumonia Obscuring the Diagnosis of Granulomatosis with Polyangiitis - Robert Ali; Candice Baldeo; Jesse Onyenekwe; Roshan Lala; Cristian Landa; Anwer Siddiqi (Case Reports in Rheumatology)
Granulomatosis with polyangiitis (GPA), previously termed Wegener’s Granulomatosis, is an autoimmune small vessel vasculitis which is highly associated with antineutrophil cytoplasmic antibodies (ANCA) and has varied clinical manifestations. Diagnosis hinges on identifying a combination of clinical features of systemic vasculitis, positive ANCA serology, and histological evidence of necrotizing vasculitis, necrotizing glomerulonephritis, or granulomatous inflammation from a relevant organ biopsy. The American College of Rheumatology has also developed a classification criteria focusing specifically on nasal or oral inflammation, abnormal chest radiograph, and abnormal urinary sediment, along with granulomatous inflammation, which helps to distinguish GPA from other forms of systemic vasculitis. In the case presented below, the diagnosis of GPA was delayed as the patient had a concomitant atypical endobronchial carcinoid which predisposed to postobstructive pneumonia. Fortunately, the papular lesions that developed across her lower limbs prompted further investigations. The return of appropriate serology coincided with progression to alveolar hemorrhage, offering a more complete clinical picture, and when she responded to the combination of steroid, cyclophosphamide, and plasma exchange, the diagnosis of GPA was cinched.